Pelaksanaan Izin Pertambangan Rakyat di Sungai Progo - Putra Harleando; Sapto Hermawan (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
Yogyakarta Special Region is a mining industry area, especially in Bantul district. One of the most popular mining commodities is the sand mining commodity along the Progo watershed. Many of the mining business actors already have permits but also many are illegal. This study aims to determine how mining business actors implement mining permits and the impacts on the surrounding environment and solutions to overcome them. This type of research used in writing this law is empirical legal research. The nature of the research used by the author in writing this law is. The objects of research in writing this law are the DIY Licensing and Investment Service, the DIY Public Works Housing and Energy Department, Mining business actors in the Progo watershed area, and the community around the mining site. Based on the results of research and discussion, the implementation of community mining permits is described into 3 (three) things, namely, the process of issuing permits by the DIY Licensing and Investment Agency, supervision procedures by the Public Works Agency for Housing and Energy and Mineral Resources, and implementation in the field by business actors. mining. The implementation of community mining permits by mining business actors is still not in accordance with the provisions in licensing and has an impact on the surrounding environment, this occurs due to a lack of legal compliance by mining business actors and a lack of supervisory personnel to carry out supervision.